Komparasi Kinerja Irigasi Tetes dan Penyiraman pada Pembibitan Kopi Arabika - Pramuhadi, Gatot; Maulana, Sidik (Jurnal Agricultural Biosystem Engineering, 2025)
Drip irrigation is one of the most widely used irrigation methods in agriculture because it delivers water directly to the plant's root zone or soil surface. This study aimed to analyze the performance of drip irrigation and compare it with conventional watering using a watering can. Twelve treatments were applied, combining four watering methods (drip irrigation with water, drip irrigation with water and nutrients, watering using a can with water, and watering using a can with water and nutrients) and three types of growing media (soil; a mixture of soil and rice husks; and a mixture of soil, husks, and manure). The results showed that the best coffee seedling growth was achieved through the drip irrigation treatment with water and nutrients on the soil, husk, and manure mixture (A2T3). This treatment resulted in a final plant height of 13.1 cm, stem diameter of 2.94 mm, 12 leaves, and a sturdiness index of 5.50. The drip irrigation system operated at a water discharge rate of 0.534 liters per minute with a water use efficiency of 75.15%. These results indicated that combining a complete growing medium with efficient irrigation and nutrient supply significantly enhanced seedling performance. In terms of cost, seedling production under drip irrigation ranged from IDR 6,450.06 to IDR 7,119.14 per seedling, while production using a watering can ranged from IDR 3,873.13 to IDR 4,645.20 per seedling. Although drip irrigation incurred higher costs, it produced higher-quality seedlings. Therefore, the use of drip irrigation with nutrients and organic-rich media is recommended as an effective and economically viable method for coffee seedling production. Keywords: Coffee Nursery, Cost Analysis, Drip Irrigation, Growing Media, Nutrients.